2014
DOI: 10.1108/ssmt-10-2013-0029
|View full text |Cite
|
Sign up to set email alerts
|

Combined loading and failure analysis of lead-free solder joints due to creep and fatigue phenomena

Abstract: Purpose – The aim of this work is the use of specially designed, authoring device to evaluate the strength of solder alloys commonly used in all kinds of electronic and electrical devices that are used in various fields of economic and industrial development to shorten the testing period. By obtaining answers to pervade science questions on how to properly investigate the reliability of solder joints can increase lifespan (uptime) of all electronic devices, and especially those that are used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…In solder joints, the formation of failure crack initiates at their corner and propagates along the region of strain concentration (Zhu et al , 2014). It is believed by different researchers in Chicot et al (2013), Jankowski et al (2014), Pei and Qu (2008a) and Ali (2015) that those solder alloys which have a better combination of strength and ductility also offer an acceptable resistance to fatigue. Based on these justifications by different researchers, along with the experimental observations in this study, it logically follows again that SAC-0.4La should show less fatigue behaviour due to lower combination of strength and ductility compared with SAC305.…”
Section: Resultsmentioning
confidence: 99%
“…In solder joints, the formation of failure crack initiates at their corner and propagates along the region of strain concentration (Zhu et al , 2014). It is believed by different researchers in Chicot et al (2013), Jankowski et al (2014), Pei and Qu (2008a) and Ali (2015) that those solder alloys which have a better combination of strength and ductility also offer an acceptable resistance to fatigue. Based on these justifications by different researchers, along with the experimental observations in this study, it logically follows again that SAC-0.4La should show less fatigue behaviour due to lower combination of strength and ductility compared with SAC305.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, multicyclic indentation test can be performed by applying a constant indentation load at the same location or by applying increasing loading between minimum and maximum loads. As an example, Jankowski et al [23] shown that under constant multicyclic indentation loading applied to a massive Lead-Sean eutectic material after 1000 cycles, the indentation depth increases following a Manson-Coffin law representative of a fatigue behavior of their material. To avoid such fatigue influence, only 100 cycles have been applied and additionally using increasing loading mode thus reducing the effect of fatigue cycle since the depth increases following the supplement of load compared to the previous one and not to a plastic accommodation of the material under the same load.…”
Section: Experimental Testmentioning
confidence: 99%
“…All types of connections used on the mentioned packaging levels must meet the reliability requirements in order to ensure long-term and appropriate operation of the device. The current research was devoted to the analysis of the solder joint reliability used at the second packaging level [12].…”
Section: Packaging and Reliability Of Solder Joints In Microelectronicsmentioning
confidence: 99%
“…This is a reason why in the case of engineering application the linear model is preferred. Figure 1 presents the hypothesis of linear damage accumulation and the problem of material hardening and softening phenomena for non-linear models [12].…”
Section: Problem Of a Damage Accumulationmentioning
confidence: 99%